Methods of Understanding The Hadith About The Prohibition of Asking for Treats from The Perspective of Yusuf al-Qardhawi - Mukhammad Alfani; Farichatul Fauziyah; Dakhirotul Ilmiyah (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This article explores the interpretation of the Hadith concerning the forbiddance of soliciting gifts, as seen through the lens of Egyptian-born Islamic scholar Yusuf al-Qardhawi, born in 1926. Al-Qardhawi's approach to interpreting Hadiths plays a crucial role in comprehending Islamic principles in daily life. A proper understanding of the Hadith should align with the directives of the Qur'an, consolidate similar traditions, and corroborate the Hadith with historical realities. The analysis of the Hadith on the forbiddance of soliciting gifts underscores the significance of harmonizing the Hadith with Qur'anic guidance for a comprehensive and coherent grasp of Islamic doctrines. Al-Qardhawi maintains a balanced perspective of the Sunnah and emphasizes the need to comprehend the Sunnah within the framework of tashri', religious studies, and civilization. The hadith's prohibition against begging reiterates it as forbidden, with exceptions for certain individuals who meet specific criteria. As such, examining the Hadith on the forbiddance of soliciting gifts from Yusuf al-Qardhawi's viewpoint offers valuable perspectives on the application of Islamic teachings in everyday life.